A comparative pitting corrosion study of mild steel in different alkaline solutions containing salts with sulphur-containing anions - Vásquez Moll, Victor Dennis (1984)
The localized corrosion of mild steel in alkaline solutions containing a salt with a sulphurcontaining anion (sodium sulphate, sodium sulphite, sodium thiosulphate, potassium thiocyanate and sodium sulphide) is studied by using potentiostatic and potentiodynamic techniques complemented with scanning electron microscopy. Alkaline solutions containing one of those salts produce pitting of mild steel at potential values more positive than those of the active-passive transition of iron in base. In the presence of either thiocyanate or thiosulphate anion iron pitting takes place through sulphide formation which reacts at the electrode surface yielding poorly protective ferrous sulphide. At potential more positive than the breakdown potential the kinetic behaviour fits a competitive surface reaction mechanism involving the formation of the passive film and the nucleation and growth of a ferrous sulphide salt layer. The proposed reaction model reproduces the corresponding experimental current-transients.